Flexible and Stretchable 3D Graphene/PDMS/PET composite film for strain sensing application - Ibrahim, Mohamad Haidar (Universiti Teknologi PETRONAS, 2016)
Strain sensor or strain gauge is device used to detect the change in electrical resistance from mechanical fundamental. There are a lot of studies developing a strain sensor using nanomaterial recently, but there are limitations on the developed strain sensor such as can only withstand limited strain before fracture, small gauge factor, leakage of liquid, complex synthesis, time consuming, and high cost.